De Schreierstoren van binnen en van buiten. Een van de laatste restanten van de Amsterdamse stadsommuring bouwhistorisch onderzocht (Bulletin KNOB, 2007)
Schreierstoren is one of the few remains of the late-medieval encircling walls of Amsterdam. Moreover, it is the only tower that was not provided with a spire in the early seventeenth century, as happened to the towers Montelbaanstoren and Munttoren. That is why Schreierstoren is still more or less in its original state. During major repairs to the exterior walls in the autumn and winter of 2005 there was the possibility for a building-historical research of the inside and outside of the tower. A horizontal joint in the brickwork indicates an interruption in the construction of the tower.During the construction of the town walls it was probably decided to close the ring around the town first, before completing the towers. The early assumption that the tower was already completed in 1486 or 1490 is not tenable. Dendrochronological research clearly indicated that the wood used for the roof construction was cut in the winter of 1498-1499, so that the tower cannot have been completed until the summer of 1499 at the earliest.Relatively little information was traced about the historical layout of the tower, due to the drastic interventions during the restoration in the years 1966-1968, without any record of the existing situation having been made. The eighteenth-century restoration by Abraham van der Hart was a project by this town architect that had not been documented so far, which also applies for the extension of the tower.